Analisis Perbandingan Kurikulum KTSP, K13 dan Kurikulum Merdeka di Sekolah Dasar - Muh Muh. Nana Supriatna; Istiqomah Eka Diyanti; Ratna Sari Dewi (Departement of Mathematics Education, 2023)
This study aims to determine the comparison of the KTSP, K 13 and independent curriculum in elementary schools. This research utilises literature research by collecting data from various sources related to the curriculum. The results of this study indicate that curriculum change is a necessity that must be faced by teachers. In addition, the curriculum also has the most important position in the world of education because the curriculum determines the process of implementing education, especially the results that must be achieved in the learning process. However, curriculum changes must be supported by facts and conditions that state the curriculum must be replaced and the curriculum must respect the teacher's teaching style and teaching methods, because the perpetrator of the curriculum is not the government but the teacher because it is the teacher who knows what to teach.